Expectation : A Francesca Fruscella Mystery - DeShell, Jeffrey (Book collections on Project MUSE., 2013)
On the surface a murder mystery-a detective's search for the killer of five people in Denver-Expectation is also, among other things, a meditation on the relationship between language and music. In his newest novel, Jeffrey DeShell draws on the musical innovations of Arnold Schoenberg-by turns traditional, serial, and atonal-to inform his grammar and language. Moving progressively through specific Schoenberg compositions, DeShell complicates the surface of his text into lyrical derivatives, all the while drawing us into a murder mystery like no other as Detective Francisca F.